THE DYNAMICS OF HADITH TRANSMISSION IN ISLAMIC LITERATURE ACROSS GENRES - Romdonny, Muhammad Rizky; Akmaluddin, Muhammad; Haris, Abdul (Nabawi: Journal of Hadith Studies, 2024)
The variety of ways in which scholars have written the hadith in their works indicates the existence of specific purposes and motivations for the choice of hadith narration in Islamic literature. This article examines the dynamics of hadith transmission historically and thematically. It focuses on two phases: the pre-tadwīn and post-tadwīn phases of the development of hadith narration; and the pattern and impact of the choice of narration in each period. This research uses qualitative analysis with library research as the source of data. As a result, it was found that there were three periods (three types of people's needs) for religious knowledge that considered the selection of hadith narration in Islamic literature. In these three periods, the writing of hadith in a field of knowledge experienced diverse and evolving trends. Like the field of exegesis which used hadith as a support for argumentation by mixing the Prophet's words with the opinions of the Companions and the fatwas of the tābi'īn, it later developed into a more systematic form with the same function. These developments show that there were adjustments in the narration of hadith in Islamic literature by considering the needs of the people as well as the function of hadith in certain scientific fields. {Ragam cara ulama menuliskan hadis dalam karyanya mengindikasikan keberadaan tujuan dan motivasi khusus atas pemilihan periwayatan hadis dalam literatur Islam. Artikel ini meneliti dinamika periwayatan hadis tersebut secara historis dan tematik. Terdapat dua fokus yang diungkap artikel ini, yaitu fase periodisasi perkembangan periwayatan hadis pra-tadwīn hadis dan pasca-tadwīn; serta pola dan dampak pemilihan periwayatan pada setiap periode. Penelitian ini menggunakan analisis kualitatif dengan sumber data pustaka (library research). Hasilnya, diketahui bahwa terdapat tiga masa (tiga jenis kebutuhan masyarakat) terhadap pengetahuan keagamaan yang menjadi pertimbangan pemilihan periwayatan hadis dalam literatur Islam. Dalam tiga masa tersebut, penulisan hadis di suatu bidang ilmu mengalami kecenderungan yang beragam dan berkembang. Seperti bidang tafsir yang menjadikan hadis sebagai pendukung argumentasi dengan mencampurkan sabda Nabi dengan pendapat sahabat maupun fatwa tābi’īn, kemudian berkembang menjadi lebih sistematis dengan fungsi yang sama. Perkembangan yang ada menunjukkan bahwa terdapat penyesuaian periwayatan hadis dalam literatur Islam dengan mempertimbangkan kebutuhan masyarakat serta fungsi hadis pada bidang keilmuan tertentu.}